Nil Santiáñez. Topographies of Fascism. Habitus, Space, and Writing in Twentieth Century Spain. Toronto: U of Toronto P, 2013. xiii + 411 pp. - Salvador Oropesa (Studies in 20th & 21st Century Literature, 2014)
Nil Santiáñez. Topographies of Fascism. Habitus, Space, and Writing in Twentieth Century Spain. Toronto: U of Toronto P, 2013. xiii + 411 pp.
Keywords: Spain; fascism; space; habitus